Evaluación de tres herbicidas post-emergentes en el cultivo de papa (Solanum tuberosum) en la zona de Mira, provincia del Carchi - Orbe Jiménez, Washington Oswaldo (2012)
In the present study aimed to examine the effect of three post-emergent herbicides in potato variety Hormuz in the San Francisco de Pisquer in the canton Mira, Carchi, whose location is 0 º 56 'North Latitude and 78 º 04 'West Longitude, at an altitude of 2.400 meters, in order to determine the effectiveness of post-emergent herbicides in the cultivation of potatoes, assess the most appropriate dose of herbicide, identify the selectivity of the molecules economic study and analyze each treatment. The design was randomized complete block (RCBD) with three replications and ten treatments. The total area of 2111,40 m2 experiment was a useful area of 11,52 m2 per experimental plot and distance between blocks and treatments of 1,50 m. The evaluations of the molecules (herbicides) under study were based on the physiological effects (phyto-incompatibility), degree of selectivity (phytotoxicity) and the degree of efficacy on weeds, arranged as follows: number of weeds (dicots and monocots), effectiveness of weed control, herbicide selectivity, percentage of weed control. Assessment physiological effects: plant height, days to flowering, number of tubers per plant, weight of tubers per plant, yield. Economic analysis was conducted based on the yield (kg / ha) and the cost of each treatment. The variables were subjected to analysis of variance and to determine the statistical difference between treatment means, we used the Tukey test at 5% level. The experimental results determined that: The best results significant compared to the control in handling dicotyledonous weed population was for the herbicide Metribuzin in the dose of 1200 cc / ha, while in monocots Haloxyfop Methyl dose of 1000 cc / ha. Herbicide treatments at different doses, showed no significant values in the effect of phytotoxicity. Herbicide treatments economic profit reached between 97 to 174% where the witness was 98%.